ANALISIS KOMUNIKASI KONSUMEN TERHADAP FIDUSIA LEASING KENDARAAN PADA STUDI KASUS DEBT. COLLECTOR DENGAN FIDUCIARY VEHICLE SYSTEM METHODS - Hefri Yodiansyah; Nanik Yuzalmi (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2018)
Debt. collector with Fiduciary Vehicle System Method with the term FVSM. With FVSM analysis system with fiducative vehicle control method as vehicle payment system in leasing system, as the pattern of business trust balance and fiduciary function. So the system of vehicle control method as fiducative vehicle payment system for fiduciary system guarantee as applied scope of vehicle business leasing system. The recognition of the system by the method of vehicle control fiducative for guarantees to prevent conflicts in the pattern of fiducative vehicle balance to study the system is more safely controlled on the fiduciary system conducted by the community. It analogy system with controlling method and supervision of vehicles fiducative to restore business trust system on pattern of fiduciary system which gives ease. With the FVSM system is a process of studying business communication systems on the pattern of vehicle control methods fiducative for guarantees to prevents conflicts in the pattern of vehicle fiducative balance to learn the system is more secure controlled on the security system asset business environment.